Plasma interaction with tungsten samples in the COMPASS tokamak in ohmic ELMy H-modes. (March 2016) - Dimitrova, M; Weinzettl, V; Matejicek, J; Popov, Tsv; Marinov, S; Costea, S; Dejarnac, R; Stöckel, J; Havlicek, J; Panek, R
Abstract: This paper reports experimental results on plasma interaction with tungsten samples with or without pre-grown He fuzz. Under the experimental conditions, arcing was observed on the fuzzy tungsten samples, resulting in localized melting of the fuzz structure that did not extend into the bulk. The parallel power flux densities were obtained from the data measured by Langmuir probes embedded in the divertor tiles on the COMPASS tokamak. Measurements of the current-voltage probe characteristics were performed during ohmic ELMy H-modes reached in deuterium plasmas at a toroidal magnetic field BT = 1.15 T, plasma current Ip = 300 kA and line-averaged electron density ne = 5×10 19 m -3 . The data obtained between the ELMs were processed by the recently published first-derivative probe technique for precise determination of the plasma potential and the electron energy distribution function (EEDF). The spatial profile of the EEDF shows that at the high-field side it is Maxwellian with a temperature of 5 – 10 eV. The electron temperatures and the ion-saturation current density obtained were used to evaluate the radial distribution of the parallel power flux density as being in the order of 0.05 – 7 MW/m 2 .